Development of PowToon Animation Video on Joyful Learning Loaded Reaction Rate Material to Increase High School Students’ Learning Motivation - Tafani, Tafani; Kamaludin, Agus (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to produce animated PowToon videos on reaction rate material withÂ Joyful LearningÂ content and to analyze the quality of the product being developed. The method used in this study used a 4-D model consisting of define, design, development, and disseminate stages, but was limited to the developing stage. The instrument used in the study was in the form of video quality assessment sheets and student responses. The data were analyzed descriptively and quantitatively. The results of video evaluation by media experts, material experts, reviewers, and student responses were 90%, 95%, 93%, and 92%, which were included in the very good category. That animated video had the advantage of being fun for students because it could present factual information through engaging animations and learning experiences that are difficult for students to get outside the school environment. Based on the study results, the PowToon animation video on the developed reaction rate material can be used as an alternative learning medium in creating fun learning and increasing student motivation.